In order to graph the parabola, first let's identify the x-coordinate of the vertex.
To do so, we can use the formula below, after identifying the parameters a, b and c from the standard form of the equation:
![\begin{gathered} x_v=(-b)/(2a) \\ \\ y=ax^2+bx+c \\ a=-3,b=0,c=3 \\ \\ x_v=(-0)/(2\cdot(-3))=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a4l4d28wzl63ywa3vftnjtc87ewnnwy5hm.png)
Now, let's calculate the points using x = -2, x = -1, x = 0, x = 1 and x = 2:
![\begin{gathered} x=-2\colon \\ y=-3(-2)^2+3=-3\cdot4+3=-12+3=-9 \\ x=-1\colon \\ y=-3(-1)^2+3=-3\cdot1+3=0 \\ x=0\colon \\ y=-3\cdot0^2+3=0+3=3 \\ x=1\colon \\ y=-3\cdot1^2+3=0 \\ x=2\colon \\ y=-3\cdot2^2+3=-12+3=-9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ykwj5dx7wx7c4uj9gquyij4qv2g7og4m6g.png)
Graphing these points and the corresponding parabola, we have: